LIPASE PRODUCTION BY PICHIA ANOMALA VTCC Y0787 USING DESIGN OF PLACKETT-BURMAN MATRIX AND CENTRAL COMPOSITE DESIGNS-RESPONSE SURFACE METHODOLOGY - Quân, Bùi Hồng; Lượng, Nguyễn Đức (Vietnam Journal of Biotechnology, 2011)
The yeast Pichia anomala VTCC Y0787 was optimized for maximum lipase production. Ihe pH optimum for this secretion was 9.0; this lipase was active in an alkaline pH range (pH > 9) and had a potential application in detergent industry. We used the design of optimum multifactorial experiments Plackett-Burman to estimate level effect of physical and chemical factors on lipase production. As the result, yeast (%), inoculum’s size (%) and vegetable oil (%) were identified as significant factors. After screening, these factors were subsequently optimized using the response surface methodology (RSM) - Central Composite Designs (CCD). These optimal levels were found out yeast extract (3.0%), inoculum’s size (2.37%; 10^ cells/ml) and vegetable oil (4.19%) in which the lipase yield was the highest. The regression equations (model) obtained and predicted maximum lipase yield 18.8078 (U/ml). We also verified model in shaking flasks (100 ml) as well as automatic fermentor (3 litres). Lipase production for 100 ml and 3 litres recorded from supernatant was 18.95 (U/ml) and 22.52 (U/ml), respectively.